Patterns of Postablation Recurrence and Adverse Cardiovascular Outcomes in Patients With Atrial Fibrillation - Sitong Li; Jingrui Zhang; Song Zuo; Jue Wang; Yiwei Lai; Mingxiao Li; Zejun Yang; Zixu Zhao; Manlin Zhao; Lan Ren; Zhen Wang; Chao Jiang; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Atrial arrhythmia recurrence after atrial fibrillation (AF) catheter ablation is conventionally assessed as a binary end point. However, the prognostic value of recurrence patterns is less studied. Methods and Results This study included patients undergoing catheter ablation from the multicenter China Atrial Fibrillation Registry study (2011–2022). Postablation AF patterns within 1 year were categorized as nonrecurrence, paroxysmal AF recurrence, or persistent AF (PersAF) recurrence. Cardiovascular outcomes included cardiovascular death, thromboembolism, and cardiovascular hospitalization. Cox proportional models with landmark analysis were used to assess the relationship between recurrence patterns and outcomes. Sensitivity analyses were conducted using Fine‐Gray models, considering death unrelated to the outcomes as the competing risk and evaluating 2‐year recurrence patterns. Among 13 811 patients (mean age, 60.5±10.8 years; 66.1% men), those with preablation PersAF, prior stroke/transient ischemic attack/systemic embolism, and increased left atrial diameter were more likely to develop PersAF postablation. Compared with nonrecurrence, PersAF recurrence was associated with higher risks of cardiovascular death (hazard ratio [HR], 2.03 [95% CI, 1.20–3.43]; P=0.009), thromboembolism (HR, 1.50 [95% CI, 1.09–2.06]; P=0.012), and cardiovascular hospitalization (HR, 1.74 [95% CI, 1.56–1.94]; P<0.001) during a median follow‐up of 3.02 years (interquartile range, 1.44–5.03 years), while paroxysmal AF recurrence was only significantly associated with an increased risk of cardiovascular hospitalization (HR, 1.98 [95% CI, 1.83–2.14], P<0.001). Sensitivity analyses yielded consistent results. Conclusions Postablation PersAF recurrence was associated with significantly higher risks of cardiovascular death and thromboembolism, compared with paroxysmal AF recurrence and nonrecurrence, indicating the prognostic importance of recurrence patterns. Registration URL: www.chictr.org.cn/; unique identifier: ChiCTR‐OCH‐13003729.